Grigoriy Grigorovich Golka - «SISJP NAMS», Staff of SI (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is devoted to the 60th anniversary of the doctor of medical sciences professor, head of the department of traumatology and orthopedics of the Kharkiv National Medical University Need for Hryhoriy Grigoryevich.